Reduction and coisotropic invariant tori of Hamiltonian systems with non-poisson commutative symmetries. I - Parasyuk, I. O. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Hamiltonian systems invariant under the non-Poisson torus action are studied on a symplectic manifold. Conditions are established under which coisotropic invariant tori filled with quasiperiodic motions exist in these systems.